Peningkatan Pengetahuan Remaja Tentang Perilaku Seksual Setelah Pendidikan Seks dan Dampaknya, Ternate, Indonesia - Muhlisa Albaar; Damir Umanailo (Poltekkes Kemenkes Padang, 2020)
In North Maluku, the death rate due to AIDS specifically Ternate is in the first place with the number of deaths 10 people from 9 existing urban districts, in the second place with the highest death rate is in North Halmahhera district with a total of 7 deaths, in third place deaths due to AIDS is West Halmahera district with a total death toll of 5 people.The purpose of this study was to determine the effect of sex education on adolescent knowledge about sexual behavior. This study uses a Pre-Experimental method, with the design of the One-Group Pre-Post Test. The results showed that before being given sex education 38.6% of students had sufficient knowledge and students who had a less knowledge were 35% and those who had good knowledge were only 26.4% of the total students. whereas after being given sex education, the results showed that students who had good knowledge drastically increased to 81.4% and students who had less knowledge were only 0.7% while students who had sufficient knowledge were only 17.9%. The Wilcoxon signed-rank test statistic test shows that P = 0.000. In Conclusion, there is an effect of providing sex education on increasing adolescent knowledge to sexual behavior. Hoped, in the future related parties can improve the quality and quantity of sex education in adolescents.